VALUE PROPOSITION ANALYSIS OF CONSUMERS' PURCHASE INTENTION - Muhammad Diah; Denny Firmansyah; Haryani Haryani; Emi Safrina (Jurnal Ekonomi, 2023)
The purpose of this study was to determine the effect of functional value, economic value, emotional value, and symbolic value on consumer buying interest at the Medan Coffee Café. The sampling technique used probability sampling with a total sample of 94 people with data collection using a questionnaire. Based on the results of the analysis, it is known that functional value, economic value, emotional value, and symbolic value have a positive and significant effect on consumer buying interest at the Kopi Kopi Café Medan, either simultaneously or partially. The results of the Determination test found an R square value of 0.796, this means that consumer buying interest in the Medan Chair Coffee Café can be explained by the variable functional value, economic value, emotional value, and symbolic value of 79.4%, while the rest (20.6%) explained by other factors outside the model.